Effect of Activation Condition on the Performance of Activated Sludge Carbon-Based Adsorbent in Diesel Desulfurization. Issue 3 (February 2020) - Jin, Mei; Hu, Bao; Tang, Xinnan; Zou, Linling; Yu, Guoxian
Abstract: Sulfur compounds in diesel oil can be removed by the adsorption technology. Based on the urban sludge as the main raw materials, activated sludge carbon-based absorbents were prepared through the cothermalization of urban sludge and rice hull by adding ZnCl2 as the chemical activator under the different activation conditions. The obtained absorbents were characterized by nitrogen adsorption characterization and were investigated in the the dibenzothiophene adsorption capacity of n-octane model oil. The characterization and the adsorption performance results showed that the amount of the micropore volume and the ratio of the micropore volume to the total pore volume played the important effects on the dibenzothiophene adsorption capacity behavior. The adsorbent could be obtained a larger amount of micropore and a bigger specific surface area, micropore specific surface and micropore volume under the activation temperature of 600 °C and the activation time of 60 min, which resulted a better behavior on the dibenzothiophene adsorption capacity of 19.9 mg S/g. The application of urban sludge in the preparation of the desulfurization adsorbent can provide a new way for the harmless and resource recovery usage.